2023
DOI: 10.1155/2023/8011189
|View full text |Cite
|
Sign up to set email alerts
|

Phytosynthesized Nanoparticles as Novel Antifungal Agent for Sustainable Agriculture: A Mechanistic Approach, Current Advances, and Future Directions

Javeria Parveen,
Tahira Sultana,
Abeer Kazmi
et al.

Abstract: Due to rapidly changing environmental conditions, virulent pathogens have arisen continuously that invades the crops and badly affects their yield and quality of the cash crops which results in economic losses. To overcome the prevalent infection of fungal pathogens, there is an utmost need to develop alternative techniques that avoid conventional agriculture practices. The use of various chemical fungicides is not an environmentally sustainable solution to fungal diseases because it produces environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“… 115 For the first time alfalfa sprouts plant extract was used for the formulation of phytosynthesized metal nanoparticles. 116 We conclude that plants are considered a highly promising and exceptional source for nanoparticles synthesis.…”
Section: Aflatoxin Detoxification Approachesmentioning
confidence: 84%
See 3 more Smart Citations
“… 115 For the first time alfalfa sprouts plant extract was used for the formulation of phytosynthesized metal nanoparticles. 116 We conclude that plants are considered a highly promising and exceptional source for nanoparticles synthesis.…”
Section: Aflatoxin Detoxification Approachesmentioning
confidence: 84%
“…144 In another study, the antifungal potential of nanoparticles is demonstrated as they produce reactive oxygen species that damage the macromolecular structures, block enzyme active sites, and inhibit all metabolic processes, which ultimately leads to cell death. 116 We summarize this mechanism by using the above-mentioned data in a graphic representation in Figure 8. However, applications of NPs in the management of AFs in the field are in the early stage.…”
Section: Role Of Nanoparticles In Aflatoxin Controlmentioning
confidence: 99%
See 2 more Smart Citations